Efeito do zinco no crescimento físico, translocação bacteriana e resposta inflamatória em ratos wistar desafiados pela dieta básica regional e diarreia osmótica - Almeida, Camila de Albuquerque (2012)
The malnutrition/diarrhea vicious cycle may result in serious consequences for human development. Studies have documented the effectiveness of zinc for diarrhea treatment. We examined the effect of oral zinc acetate (500 mg/L in drinking water) to weanling rats, challenged by under nutrition using a regional basic diet (RBD, with 9% of protein, 70% of carbohydrate, and 0.3% of fat) for two weeks and by osmotic diarrhea induced by a saturated lactose solution (given by oral gavage, 30 g/Kg) in the last 7 days. Protocols from this study were previously approved by the Ethical Committee for Animal Research of the Federal University of Ceara. Diarrheal scores were graded as follows: 0-normal stools; 1-wet stools; 2-pasty stools; 3-semiliquid stools; 4-watery diarrhea. Rat stools were checked 24h post- lactose intake. Blood was drawn for zinc serum level measurements using atomic absorption spectroscopy. Afterwards, rats were euthanized to harvest jejunum tissue for histological processing, morphological analyses of villus, crypt and villus/crypt ratio, goblet cell counts, and villin immunohistochemistry. In addition, we measured intestinal cytokine profile by ELISA from frozen samples. In a subset of animals, mesenteric lymph nodes and spleen were harvested under aseptic condition for bacterial translocation studies. The mesenteric lymph node and spleen were removed, weighed, homogenized and plated onto agar MacConkey for quantification of aerobic colony-forming units/gram. The RBD caused significant reductions in weight gain and villus height (p<0.05), significant augment of crypt depth, and reduction of the villus/crypt ratio. There were reductions in the tissue villin expression, villus brush border changes, and lower goblet cell numbers with RBD challenge. Furthermore, the RBD challenge reduced zinc serum levels with hematological alterations and significant higher jejunal IL-1β, IL-10, and TNF-α levels. The compound effect of saturated lactose solution and RBD induced osmotic diarrhea and weight gain loss, however with increased serum zinc levels and same inflammatory status. There was a significant bacterial translocation to the lymph nodes and spleen induced by RBD and lactose challenge, albeit with histology improvement, increased villin expression and goblet cell counts. Zinc supplementation improves weight gain only with osmotic diarrhea. Zinc treatment improved villus height and crypt depth only in the DBR-undernourished group without diarrhea. However, the villus:crypt ratio was improved in both groups by zinc supplementation. Furthermore, villin expression was higher in the zinc-treated undernourished control group. Zinc supplementation reduced the jejunal inflammatory cytokine levels and diarrhea scores with lower bacterial translocation in the RBD and lactose group and supplemented with zinc. Altogether, our findings support the use of zinc supplementation to break the vicious cycle of diarrhea and malnutrition in children.